Superior Semicircular Canal Dehiscence Syndrome in a Woman: A Case Report - Arif Surgana; Haris Mayagung Ekorini (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Superior semicircular canal dehiscence (SSCD) syndrome is a disease that occurs veryrare. Clinical presentation consists of Tullio’s phenomenon and Hennebert’s sign. This case presentationis atypical and clinician should be aware. Purpose: to present the rare case of Superior semicircular canaldehisence (SSCD) Case presentation: A 65-year-old woman with complaints of dizziness from 2 years agoand her recurrence. The audiogram showed bilateral sensorineural deafness with a mean hearing thresholdof 58 decibels (dB) of the right ear and 48 dB of the left ear. There is also an air-bone gap in the right earat low frequencies (250 Hz). The tympanogram revealed a type A result in both ears. Positive results wereobtained on the examination of Romberg sharpened, positive Fukuda step to the right, and the Gans test. CTscan showed dehiscence of the right superior semicircular canal. Therapy in patients was given conservativetherapy because the participants refused to undergo surgery. Conclusion: SSCD has a specific symptom ofTullio’s phenomenon and CT scan shows dehiscence of the superior semicircular canal.